Accuracy and Efficacy of a Patient-Specific Drill Guide Template System for Lumbosacral Junction Fixation in Medium and Small Dogs: Cadaveric Study and Clinical Cases - Fujioka, Toru; Nakata, Kohei; Nakano, Yukiko; Nozue, Yuta; Sugawara, Taku; Konno, Naoyuki; Maeda, Sadatoshi; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2020)
Objectives: To develop drill guide templates as an intraoperative guide, and to evaluate the accuracy and safety of screw placement in the lumbosacral junction. Samples: Canine cadaveric specimens of the lumbosacral junction (n=6), and clinical cases of lumbosacral instability (n=3). Procedures: Computed tomography data of the lumbosacral region of cadaveric specimens and clinical cases were obtained. The optimum screw trajectories were determined and drill guide templates were fabricated using a three-dimensional printing system. Drill holes were made using the templates in cadaveric specimens and clinical cases, and lumbosacral fixation was performed in clinical cases. Computed tomography images were obtained to compare the planned and postoperative drill hole trajectories, and the accuracy and safety of drilling and screw placement in the lumbosacral junction were evaluated. Results: Thirty-six drill holes were made in cadaveric specimens. The overall mean drill hole deviation was 2.05 ± 1.32 mm. A total of twelve screws were placed in the lumbosacral junctions of three clinical cases. The overall mean drill hole deviation was 2.43 ± 1.09 mm. Clinical signs improved within two weeks in the clinical cases. All drill holes were completely located within the bone in cadaveric specimens and clinical cases. Conclusion and Clinical Relevance: The surgical procedures using the drill guide templates were performed safely with good clinical outcomes. The drill guide template system provided useful surgical guidance to safely and precisely perform screw placement for lumbosacral fixation surgery in small dogs.